Perceived Mortality and Perceived Morality: Perceptions of Value-Orientation Are More Likely When a Decision Is Preceded by a Mortality Reminder - Nordmo, Mads; Norman, Elisabeth (Frontiers in Psychology, 2016)
The questions addressed in this paper are whether and how reported mortality reminders can function as an indication of sincerity when communicating ambiguously motivated decisions. In two experiments, participants were exposed to a fictitious CEO who announced a decision to implement new organizational measures that were both environmentally and financially beneficial. In the experimental condition, the CEO attributed her new ideas to a recent mortality reminder. In the active control condition, the CEO attributed her decision to a non-lethal dentistry health scare, and in the passive control condition the CEO did not give any account of events preceding her decision. When a CEO implemented new corporate initiatives after a mortality reminder, her motivation for doing so was perceived as somewhat more motivated by intrinsic values, and significantly less motivated by financial gains. This change in attribution patterns was demonstrated to be indirectly related to a positive evaluation of the CEO, as well as an increased willingness to pay for the organization’s services. The second experiment further demonstrated that the reduced attribution to financial motivation associated with mortality awareness persisted even when the CEO in question was known for placing a high personal priority on financial goal attainment. The findings underscore the importance of perceived value-oriented motivation when communicating climate change mitigating policies, and the role of mortality awareness as one of many ways to induce such attributions.